A Sosialisasi Purna Perkerja Migran Indonesia (PMI) dalam Meningkatkan Ekonomi Masyarakat - Mohammad Rizal; Rois Arifin; Afi Rachmat Slamet; Arini Fitria Mustapita (Universitas Mathla'ul Anwar Banten, 2022)
SOCIALIZATION OF PURNA PEKERJA MIGRAN INDONESIA (PMI) IN IMPROVING THE COMMUNITY ECONOMY. Data from the Badan Pusat Statistik (BPS) shows that the number of unemployed in Indonesia is increasing due to the Covid-19 pandemic. The program for placing workers abroad is one alternative to reduce unemployment in the country. However, the role of Purna PMI's efforts on community economic development in Malang Regency has not been widely studied. With this service, it is hoped that it will be known how mu ch the efforts of Purna PMI have played a role in expanding job opportunities, empowering the community's economy. The method used in this research is the Community Based Interactive Approach Method (CBIA). The socialization was carried out by providing material on the community's economy from the perspective of Management, Employment, Organization and Banking. The program was chosen because it is considered important and is expected to provide education to Retired PMI. With the implementation of the socialization program regarding the improvement of the community's economy, all parties benefit, especially for the Retired PMI Malang Regency. Overall, the implementation of the socialization can be said to be successful because the participants were able to master it, as evidenced by the distribution of questionnaires to the participants and the comparison of the percentage before and after the socialization that was obtained with the figure before socialization was 21% and after socialization was 84%.